Brain Protection by Methylene Blue and Its Derivative, Azur B, via Activation of the Nrf2/ARE Pathway in Cisplatin-Induced Cognitive Impairment - Ekaterina P. Krutskikh; Daria V. Potanina; Natalia A. Samoylova; Mariya V. Gryaznova; Irina S. Sadovnikova; Artem P. Gureev; Vasily N. Popov (MDPI AG, 2022)
Cisplatin is a cytotoxic chemotherapeutic drug that leads to DNA damage and is used in the treatment of various types of tumors. However, cisplatin has several serious adverse effects, such as deterioration in cognitive ability. The aim of our work was to study neuroprotectors capable of preventing cisplatin-induced neurotoxicity. Methylene blue (MB) and AzurB (AzB) are able to neutralize the neurotoxicity caused by cisplatin by protecting nerve cells as a result of the activation of the Ntf2 signaling pathway. We have shown that cisplatin impairs learning in the Morris water maze. This is due to an increase in the amount of mtDNA damage, a decrease in the expression of most antioxidant genes, the main determinant of the induction of which is the Nrf2/ARE signaling pathway, and genes involved in mitophagy regulation in the cortex. The expression of genes involved in long-term potentiation was suppressed in the hippocampus of cisplatin-injected mice. MB in most cases prevented cisplatin-induced impairment of learning and decrease of gene expression in the cortex. AzB prevented the cisplatin-induced decrease of genes in the hippocampus. Also, cisplatin induced disbalance in the gut microbiome, decreased levels of Actinotalea and Prevotella, and increased levels of Streptococcus and Veillonella. MB and AzB also prevented cisplatin-induced changes in the bacterial composition of the gut microbiome.